Comparative analysis of two hazard rainstorm processes in Hunan affected by the Southwest China vortex. Issue 1 (October 2021) - Hu, Yan; Liu, Hongwu; Liu, Huanqian; Tang, Minghui; Zeng, Yuting
Abstract: Based on surface rain-gauge data, Doppler radar products, the National Center for Environmental Prediction (NCEP) reanalysis data and other multi-source datasets, two regional rainstorm processes caused by the Southwest China vortex (SCV) in June, 2015 are diagnosed and analyzed from the aspects of water vapor condition, dynamic and thermodynamic mechanisms, and the causes of the regional rainstorms are discussed. The results show that the two processes belong to the SCV rainstorm, and there is the southwest jet in the middle and lower levels. The high-value area of water vapor flux and the water vapor convergence center can well indicate the rainstorm area. In the first process, two water-vapor-flux transport bands from the Bay of Bengal and the South China Sea converge. In the second process, the water vapor mainly comes from the Bay of Bengal. The extreme values of dynamic and thermodynamic factors all appear near 850 hPa in the rainstorm development stage, and the latitudes of the extreme values are close to the severe rainfall area. The first process has a typical rainstorm vorticity configuration with negative vorticity at upper layer and positive vorticity at lower layer. The second process is mainly driven by the strong positive vorticity at the lower layer. There are strong energy frontal zones near the ground, and the rainstorm area is consistent with the convergence region of cold and warm air. The characteristics of radar echo show that there are mid-level and low-level jet streams in the two rainstorm processes. The first process is dominated by the cumulus precipitation, and the adverse wind region promotes the development of the rainstorm. The second process is dominated by cumuliform-stratiform-mixed cloud precipitation, and the train effect is the main cause of the regional rainstorm.